The impact of strength level on adaptations to combined weightlifting, plyometric, and ballistic training - James, L. P.; Haff, G. G.; Kelly, V. G.; Connick, M. J.; Hoffman, B. W.; Beckman, E. M. (Scandinavian Journal of Medicine & Science in Sports, 2018)
The purpose of this investigation was to determine whether the magnitude of adaptation to integrated ballistic training is influenced by initial strength level. Such information is needed to inform resistance training guidelines for both higher- and lower-level athlete populations. To this end, two groups of distinctly different strength levels (stronger: one-repetition-maximum (1RM) squat = 2.01 ± 0.15 kg·BM-1; weaker: 1.20 ± 0.20 kg·BM-1) completed 10 weeks of resistance training incorporating weightlifting derivatives, plyometric actions, and ballistic exercises. Testing occurred at pre-, mid-, and post-training. Measures included variables derived from the incremental-load jump squat and the 1RM squat, alongside muscle activity (electromyography), and jump mechanics (force-time comparisons throughout the entire movement). The primary outcome variable was peak velocity derived from the unloaded jump squat. It was revealed that the stronger group displayed a greater (P = .05) change in peak velocity at mid-test (baseline: 2.65 ± 0.10 m/s, mid-test: 2.80 ± 0.17 m/s) but not post-test (2.85 ± 0.18 m/s) when compared to the weaker participants (baseline 2.43 ± 0.09, mid-test. 2.47 ± 0.11, post-test: 2.61 ± 0.10 m/s). Different changes occurred between groups in the force-velocity relationship (P = .001-.04) and jump mechanics (P = .05), while only the stronger group displayed increases in muscle activation (P = .05). In conclusion, the magnitude of improvement in peak velocity was significantly influenced by pre-existing strength level in the early stage of training. Changes in the mechanisms underpinning performance were less distinct.